Xi Jinping's Foreign Policy After the 20th Congress of the Chinese Communist Party in Public Policy Analysis - Surryanto Djoko Waluyo; Sembiring, Afri Emilia Br (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
This article explores the transformation of China’s foreign policy under Xi Jinping following the 20th National Congress of the Chinese Communist Party (CCP), emphasizing the link between domestic power consolidation and international strategic behavior. Theb problem addressed is how Xi’s strengthened political control has influenced the formulation and implementation of foreign policy in the context of a more centralized and ideologically driven governance model. Using a qualitative research method and literature review approach, this study integrates foreign policy theories—particularly the Rational Actor Model and Role Theory—with public policy frameworks such as the Multiple Streams Framework (MSF) and the Advocacy Coalition Framework (ACF). The findings reveal that Xi’s consolidation of power has led to a foreign policy that is more assertive, nationalistic, and closely aligned with the party’s domestic priorities, including national security and technological self-reliance. Foreign policy formulation and implementation have become increasingly centralized, enabling strategic agility with minimal internal resistance. The study concludes that China’s foreign policy is not only shaped by external geopolitical pressures but also by internal political dynamics and ideological narratives, making it essential to analyze it through both international and domestic policy lenses.